Fortification of wheat biscuits with vitamin C and phosphorus from ampalaya (Momordica charantia Linn) powder. - Naciongayo, Danielle Mendoza
Freeze-dried ampalaya powder was used as a fortificant of wheat biscuits. Biscuits were processed at varying amounts of ampalaya powder with a fixed amount of wheat four. Three treatments were used: Treatment 1 (2% ampalaya powder), Treatment 2 (4% ampalaya powder), and Treatment 3 (6% ampalaya powder). Treatment 1 was considered as the most preferred formulation. Its proximate composition (%) was composed of moisture content, 24.2; crude protein, 9.35; crude fat, 20.9; ash, 2.72; crude fiber, 1.61 and carbohydrates, 41.2. Its vitamin C and phosphorus content were 0.9 mg and 0.08 ppm, respectively. Two sample t-test revealed a significant difference in terms of crude fiber and respectively. Two sample t-test revealed a significant difference in terms of crude fiber and vitamin C content between Treatment 1 and control. T-test also revealed that there was no significant difference between Treatment 1 and contro in terms of moisture, fat, ash, protein, carbohydrate and potassium content. Treatment 1 obtained a like moderately rating in the General Acceptability test. Treatment 1, with moderate ampalaya flavor and no perceptible ampalaya odor, was brown in color with moderate amount of ampalaya powder that was not uniformly distributed. Biscuits were slightly crumbly and moderately sweet. Despite the lack of significant difference in the improvement of the physico-chemical and nutritional properties, addition of ampalaya powder still affected the composition of the fortified wheat biscuits. Also, freeze-drying retained the nutritional content of ampalaya. However, the bitterness from ampalaya afected the sensory characteristics of the product. Thus rendering the wheat biscuit to be only liked moderately. Increasing the amount of ampalaya powder could affect the acceptability of the product.